2021
DOI: 10.1021/acsinfecdis.1c00366
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of a Klebsiella Bacteriophage Receptor-Binding Protein as a Superior Biorecognition Molecule

Abstract: Klebsiella pneumoniae is a Gram-negative bacterium that has become one of the leading causes of life-threatening healthcare-associated infections (HAIs), including pneumonia and sepsis. Moreover, due to its increasingly antibiotic resistance, K. pneumoniae has been declared a global top priority concern. The problem of K. pneumoniae infections is due, in part, to the inability to detect this pathogen rapidly and accurately and thus to treat patients within the early stages of infections. The success in bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 86 publications
(165 reference statements)
2
10
0
Order By: Relevance
“…We found that the genomes were arranged in a particular disposition: no lysis-specific blocks were distinguished, and structural and morphogenesis-related proteins were repeated in various blocks along the genome (Figure 2). This type of genome, which is not very well organized into functional clusters but shows dispersed agglomerates, has previously been described for big phages of K. pneumoniae, also belonging to the Tevenvirinae subfamily, within which the T4 coliphage is the best studied [19].…”
Section: Genomic Analysis and Comparison Of The Phages Vb_kpnm-vac13 And Vb_kpnm-vac66mentioning
confidence: 59%
“…We found that the genomes were arranged in a particular disposition: no lysis-specific blocks were distinguished, and structural and morphogenesis-related proteins were repeated in various blocks along the genome (Figure 2). This type of genome, which is not very well organized into functional clusters but shows dispersed agglomerates, has previously been described for big phages of K. pneumoniae, also belonging to the Tevenvirinae subfamily, within which the T4 coliphage is the best studied [19].…”
Section: Genomic Analysis and Comparison Of The Phages Vb_kpnm-vac13 And Vb_kpnm-vac66mentioning
confidence: 59%
“…Thus, the phage tail fiber protein shows a wider host spectrum than the lytic phages because phage infection requires more complex steps. 28 It has been reported that the phage tail spike protein and endolysin have been used as molecular recognition probes for the detection of pathogenic bacteria. 29,30 However, both the proteins show strong lytic activity, which leads to a significantly decreased capture efficiency to the bacterial cells in short time.…”
Section: ■ Introductionmentioning
confidence: 99%
“…On the cellular surface of Gram-negative pathogens, many proteins, oligosaccharides, and lipopolysaccharides (LPSs) are capable of acting as the binding receptors for lytic phages. , Lytic phages can attach to some non-host bacteria but not cleave them because their high specificity to the host bacteria may be due to the progeny biosynthesis phase rather than the adsorption phase. Thus, the phage tail fiber protein shows a wider host spectrum than the lytic phages because phage infection requires more complex steps . It has been reported that the phage tail spike protein and endolysin have been used as molecular recognition probes for the detection of pathogenic bacteria. , However, both the proteins show strong lytic activity, which leads to a significantly decreased capture efficiency to the bacterial cells in short time.…”
Section: Introductionmentioning
confidence: 99%
“…Most phages were found to have a typical organization of the genome in functional modules, as previously described (2, 51, 52). By contrast, members of the Myoviridae family, which are included in the “larger phages” (> 100 bp), did not present specific lysis blocks, and structural and morphogenesis-related proteins were repeated in several blocks throughout the genome (38, 53). The genomes of all phages had endolysins and holins, proteins that are responsible for degradation of the bacterial cell wall during the infection by the host to facilitate the exit of the phage progeny (54).…”
Section: Discussionmentioning
confidence: 97%